1999
DOI: 10.1177/000348949910800509
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Role of Peptide Leukotrienes and Histamine in the Development of Nasal Mucosal Swelling in Nasal Allergy

Abstract: To evaluate the importance of histamine and peptide leukotrienes (LTs) in the development of nasal mucosal swelling in nasal allergy, H1 receptor antagonist (mequitazine, 6 mg, in 2 divided doses, Rhône-Poulenc Rorer, France) and LT receptor antagonist (ONO-1078, pranlukast, 450 mg, in 2 divided doses, Ono Pharmaceutical Co, Ltd, Osaka) were administered orally for 7 days to 16 subjects with perennial nasal allergy to house dust mites, and the effects of receptor blockers of these chemical mediators on the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 19 publications
2
38
2
Order By: Relevance
“…Because sneezing and watery rhinorrhea in allergic rhinitis could be inhibited by treating patients with antihistaminics, these symptoms are triggered mainly via the stimulation of nasal terminals of the trigeminus nerve by histamine (4). Although the detailed sequence of events leading to the occurrence of allergic nasal blockage are not yet fully elucidated, it has been reported that a cysteinyl leukotriene (CysLT)-receptor antagonist reduced nasal blockage (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Because sneezing and watery rhinorrhea in allergic rhinitis could be inhibited by treating patients with antihistaminics, these symptoms are triggered mainly via the stimulation of nasal terminals of the trigeminus nerve by histamine (4). Although the detailed sequence of events leading to the occurrence of allergic nasal blockage are not yet fully elucidated, it has been reported that a cysteinyl leukotriene (CysLT)-receptor antagonist reduced nasal blockage (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Bisgaard et al (13) demonstrated that, even in normal control subjects, a high dose of LTD4 may induce nasal mucosal blood flow and NAR in the absence of nasal discharge. Furthermore, Numata et al (19) reported that nasal mucosal swelling induced by nasal challenge was prevented by LTRA administration.…”
Section: Discussionmentioning
confidence: 99%
“…Miadonna et al (20) and Howarth (21) demonstrated that the symptoms of AR such as nasal secretion, nasal obstruction in particular, was more strongly correlated with the release of arachidonic acid metabolites than histamine in the nasal secretion or specimen during natural exposure. However, when stimulated with histamine or cysLT there was a different result; sneezing, itching, rhinorrhea and nasal obstruction could be induced by histamine rapidly (within a few seconds), while cysLT caused a more pronounced and longer lasting nasal obstruction (13,19). These phenomena implied that not only one, probably many mediators were involved in the development of symptoms, even involved with nervous reflex.…”
Section: Discussionmentioning
confidence: 99%
“…However, the oral doses of olopatadine that inhibited the increase in histamine and lipid mediators in NALF after antigen challenge in sensitized guinea pigs were nearly equivalent to the doses that inhibited the experimental allergic rhinitis in guinea pigs. Recently, the involvement of peptide LTs and TXA 2 have been suggested because pranlukast, a peptide LTs-receptor antagonist and ramatroban, a TXA 2 -receptor antagonist, showed clinical efficacy in the treatment of nasal obstruction (34,35). Consequently, it is thought that the inhibitory effects of olopatadine on the release of peptide LTs and TX may contribute to the suppressive effect of olopatadine on nasal obstruction.…”
Section: -2 Mode Of Action 2-2-1 Histamine H1-receptor Antagonistimentioning
confidence: 99%